Pemanfaatan Video TikTok sebagai Media Pembelajaran Interaktif untuk Meningkatkan Penguasaan Mufradat Siswa - Safitri, Syaila Ayu; Huda, Hisbullah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
The low mastery of Arabic vocabulary among tenth-grade students at MAN 1 Gresik, where only 45% achieved the minimum mastery criterion, indicates the need for innovative digital learning media that align with Generation Z learning characteristics. This study aimed to examine the effectiveness of TikTok video media (audio-visual, song-based content) in improving students’ Arabic vocabulary (mufradat) mastery on the topic of al-hiwāyah (hobbies). A quantitative approach was employed using a quasi-experimental nonequivalent control group design with pretest–posttest measures. The sample comprised 36 students in class X-12 as the experimental group and 37 students in class X-10 as the control group. Data were collected using a validated multiple-choice vocabulary test and analyzed using the Shapiro–Wilk normality test, Levene’s homogeneity test, and an independent-samples t-test to compare posttest scores between groups. Results showed that the experimental group’s mean score increased from 79.2 (pretest) to 91.2 (posttest), while the control group’s mean score increased from 77.4 to 89.3. The independent-samples t-test indicated a significant difference in posttest scores between the experimental and control groups (Sig. 2-tailed = 0.002). These findings suggest that TikTok-based video media effectively enhances students’ Arabic vocabulary mastery and supports learning engagement, although implementation requires supervision to reduce distractions and must consider constraints related to short video duration and internet access.